甘油酯型n-3多不饱和脂肪酸富集方法研究进展Progress on enrichment methods of glyceride-type n-3 polyunsaturated fatty acids - 陈烨1，黄璟雯1，王熠璠1，黄家祺1，李康宁1，李才明1，王小三1，杨兆琪2 CHEN Ye1, HUANG Jingwen1, WANG Yifan1, HUANG Jiaqi1, LI Kangning1, LI Caiming1, WANG Xiaosan1, YANG Zhaoqi2 (Zhongguo youzhi, 2022)
n-3多不饱和脂肪酸（n-3 PUFA）具有多种生理活性，其主要有3种存在形式，其中甘油酯型n-3 PUFA因其生物利用度高和不易被氧化而优于游离型和乙酯型。然而，目前鲜有对甘油酯型n-3 PUFA进行高纯度富集的方法。为了对甘油酯型n-3 PUFA的高值化更加深入的研究提供参考，综述了富集甘油酯型n-3 PUFA的3种常见方法（物理一步法、两步法和酶一步法）及优缺点。物理一步法可以避免产物氧化，但得率较低；两步法工艺复杂，并有可能产生环境污染；而酶一步法具有简单、高效等优点，成为学者们关注的焦点。现有脂肪酶对甘油酯型n-3 PUFA的富集能力有限，还需进一步发掘富集能力更强的选择性脂肪酶 There are three main forms of n-3 polyunsaturated fatty acids (n-3 PUFA) with a variety of physiological activities, of which glyceride-type n-3 PUFA is superior to free and ethyl ester forms due to its high bioavailability and less susceptibility to oxidation. However, there is few method for the enrichment of glyceride-type n-3 PUFA with high purity. In order to provide a reference for a more in-depth study of the high value of glyceride-type n-3 PUFA, three common methods (physical one-step, two-step and enzymatic one-step), and their advantages and disadvantages of enriching glyceride-type n-3 PUFA were reviewed. The physical one-step method can avoid product oxidation, but the yield is low; the two-step method is complicated and may produce environmental pollution; while the enzymatic one-step method has the advantages of simplicity and high efficiency, which has become the focus of scholars attention. The existing lipases are limited in their ability to enrich glyceride-type n-3 PUFA, and there is a need to further explore selective lipases with higher enrichment capacity.